2009
DOI: 10.1038/cdd.2009.87
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrimidine tract binding proteins (PTB) regulate the expression of apoptotic genes and susceptibility to caspase-dependent apoptosis in differentiating cardiomyocytes

Abstract: Cardiac morphologic abnormalities in mice deficient for key regulators of the caspase-dependent signaling underscored its role in heart development. However, the mechanisms regulating apoptotic gene expression in the developing heart are unknown. As polypyrimidine tract binding proteins (PTB) determine gene isoform expression during myoblast differentiation and contribute to Apaf-1 translation in cell lines, we investigated whether PTB regulate apoptotic gene expression in differentiating cardiomyocytes. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…The loss of CLK1 activity may disrupt a feedback loop because its kinase activity is critical for the phosphorylation of multiple SR proteins that regulate splicing (63,70,71). The inclusion of CASP3 exon 2 with EWS-FLI1 reduction places an internal ribosome entry site into the 5′-UTR of the mRNA (72). This 5′-UTR may enhance the translation of caspase-3, thus increasing its protein levels and in part explaining the increased apoptosis seen with YK-4-279 treatment (21).…”
Section: Yk-4-279 Alters Splicing Rather Than Direct Transcriptional mentioning
confidence: 99%
“…The loss of CLK1 activity may disrupt a feedback loop because its kinase activity is critical for the phosphorylation of multiple SR proteins that regulate splicing (63,70,71). The inclusion of CASP3 exon 2 with EWS-FLI1 reduction places an internal ribosome entry site into the 5′-UTR of the mRNA (72). This 5′-UTR may enhance the translation of caspase-3, thus increasing its protein levels and in part explaining the increased apoptosis seen with YK-4-279 treatment (21).…”
Section: Yk-4-279 Alters Splicing Rather Than Direct Transcriptional mentioning
confidence: 99%
“…While Kalsotra et al ( 2008 ) reported that their levels do not change from PN1 to adult stages, Zhang et al ( 2009 ) and Ye et al ( 2013 ) demonstrated its downregulation in rat and mouse. A correlation between the PTB developmental downregulation and the developmental downregulation of apoptotic genes was demonstrated in mouse (Zhang et al 2009 ). Consistently, over-expression of PTB in adult CM induces the expression of pro-apoptotic proteins without affecting their transcript levels suggesting that PTB regulates translation of apoptotic genes.…”
Section: Ptb Proteinsmentioning
confidence: 85%
“…When PTB is re-expressed in CM, caspase activity is enhanced and ischemia triggers caspase-dependent DNA fragmentation. By contrast, in the absence of PTB differentiated CM show caspaseindependent DNA fragmentation (Zhang et al 2009 ). These results suggest that PTB proteins play important roles in CM maturation similarly to what has been shown in C2C12 myoblast and neuron differentiation (Boutz et al 2007a , b ;Makeyev et al 2007 ).…”
Section: Ptb Proteinsmentioning
confidence: 93%
See 1 more Smart Citation
“…Ptb nucleotide sequence GCACAGTC CTGAAGATCAT was chosen for PTB-specific expression silencing using free RNAi design interfaces and has been validated previously [28]. Primers for small hairpin RNA interference (shRNA) were subcloned into the pLVTHM plasmid as described before [28]. pEIGW or pLVTHM constructs were transfected into HEK293T packing cell line and tittered as described previously [28].…”
Section: Ptb Overexpression and Knockdownmentioning
confidence: 99%